PENERAPAN RELIABILITY CENTERED MAINTENANCE (RCM) PADA POROS RODA DEPAN ISUZU TYPE cxz-51 - Aris Fiatno; Denur Denur (Research Center University of Pahlawan Tuanku Tambusai, 2018)
Breakdown of freight on the front wheel axle truck type cxz-51, Reliability Centered Maintenance (RCM) method is expected to define the maintenance schedule and know the exact action of maintenance activities. How to determine optimal maintenance measures for the front wheel axle to have a long service life according to performance standards using the Reliability Centered Maintenance (RCM) approach. Methods of data collection is done by several methods which include the following: Conduct a direct survey of spaciousness and communicate with the driver of the vehicle about the problem that occurred, where and chronology of events as well as data collection according to the history of steering system truck cxz-5, the method of data processing using pareto diagram. The critical component of the sub-assembly of the cxz-51 isuzu steering system can be seen in the figure below, where the bearing com undergoes wear on the inner diameter of the bearing causing the gap between the steering knucle pin and the bearing com to be loose resulting in the bearing undergoing axial and radial pressure causing the collision between the wheel drum with steering knucle.